Evaluación del daño de formación en la zona de near wellbore de pozos productores, para un campo colombiano ubicado en la cuenca de los Llanos Orientales. (2022)
The study presented in this document had as its fundamental purpose to evaluate the formation damage in the near wellbore zone of the producing wells of the K1 formation of the Llanos Orientales basin for the Apiay-Suria area according to the passage of time in comparison with a study previous carried out in 2012. For the development of the study, three (3) wells were selected from the area in question in order to obtain results that represent the formation damage present along the K1 producing sand. The selection of the wells is carried out by means of a ranking in macros designed by the reservoir engineers of the company Ecopetrol S.A. which consists of the evaluation of certain parameters that assign a score to each well for subsequent selection.